Exploring ancient leadership guidelines : The significance of Kautilya’s Arthashastra in modern business practices - Vinnakota, Sai Veekshita; Martínez Pantoja, Yadira Ixchel; Kloudová Jiřičková, Václava; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis analyzes the relevance of Kautilya’s Arthashastra and its value-based leadership framework in the modern business environment. The purpose of the thesis is to explore the applicability of the value-based framework and assess the extent of its versatility in Small and Medium-sized Organizations (SMOs) within the Czech Republic and India. A mixed-methods approach was utilized for research. First, in-depth qualitative data were gathered through semi-structured interviews with leaders of SMOs. To complement this, quantitative data was utilized by collecting data from closed-ended surveys distributed to employees within this business context. The research found that Kautilya’s value-based framework was quite prominent in the SMO environment and was suggested as a foundation for leadership development in SMOs.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses